Low urinary dopamine excretion associated to low sodium excretion in normotensive Piaroa Amazonian ethnia compared to urban subjects - Romero Vecchione, Eduardo; Vásquez, José; Lema, Gonzalo; Guerrero, Hilda; Rosa, Francisco; Bermúdez, Mélida (Investigación Clínica, 2013)
Â The objective of this work was to compare urinary doparnine, noradrenaline, adrenaline. sodium and potassium excretion in a group of normotensive Piaroa Amazonic ethnia who do not use salt in their regular food intake, against a group of urban normotensive citizens known to have a high salt intake in their regular meals. Twenty adult normotensive Piaroa subjetcs living in the Amazonas forest, 11 men and 9 women, 23-72 years old, and 33 normotensive urban citizens, 25-70 years old, 17 men and 17 women, were included in the study. After a 10 min. rest, an average of three supine systolic (SBP) and diastolic (OBP) blood pressure recordings was obtained. Piaroas subjects SBP and OBP were 111.3Ó 2.9 mmHg and 62.7Ó 1.9 mmHg respectively; urban subjects SBP and OBP were 111.8 Ó 2.2 rnrnHg and 70.3 Ó 1.6 mmHg respectively. Supine heart rate was lower in Piaroas (58.0 Ó 1.8 beats/min) than in urban subjects (76.5Ó 1.9 beats/min), p < 0.05. Sodium urinary excretion was much lower in Piaroas (12.6 Ó 5.2 rnrnol/24 h) when compared to urban subjects (210.7 Ó 24.5 mmol/24 hl. p < 0.01. No difference was found in daily urinary potassium excretion between Piaroas and urban subjects (50.4 Ó 7.2 mmol/24 h vs 45.1Ó 7.4 mmol/24 h). Urinary dopamine excretion was lower in Piaroas (314.7 Ó 40.1 J..lg/24 h) in comparison to urban subjects (800.4Ó 59,2 J..lg/24h). p < 0.05. Oaily urinary noradrenaline and adrenaline excretion were 67.9 %and 85.4% respectively lower in Piaroas than in urban subjects. In conclusion, lower amounts of sodium daily intake are associated to lower kidney dopamine production in Piaroas as compared to urban subjects. Apparently indigenous tribes might require less kidney dopamine synthesis to excrete the very small amounts of salt they consume in their regular food intake. The oppositewas found in urban subjects; more kidney dopamine synthesis would be required for larger amounts of urinary sodium excretion. In this population, essential hypertension has been associated to a failure of the natriuretic mechanism triggered by dopamine on kidney tubules.